The Effect of Dose and Quality Assurance in Early Prostate Cancer Treated with Low Dose Rate Brachytherapy as Monotherapy. Issue 7 (July 2015) - Henry, A.M.; Rodda, S.L.; Mason, M.; Musunuru, H.; Al-Qaisieh, B.; Bownes, P.; Smith, J.; Franks, K.; Carey, B.; Bottomley, D.
Abstract: Aims: To examine the relationship between post-implant computed tomography dosimetry and long-term prostate-specific antigen relapse-free survival in patients treated with iodine 125 (I-125) low dose rate prostate brachytherapy as monotherapy and, second, to audit recent practice against Royal College of Radiologists' (RCR) guidelines after the re-introduction of post-implant dosimetry for all patients in our centre. Materials and methods: Between March 1995 and September 2007, 2157 consecutive patients with localised prostate cancer underwent I-125 permanent prostate brachytherapy as monotherapy in a single UK centre. All patients were transrectal ultrasound planned delivering a 145 Gy (TG 43) minimum peripheral dose. None received supplemental external beam radiotherapy. Post-implant computed tomography-based dosimetry was undertaken between 4 and 6 weeks after treatment and was available for 711 (33%). Outcomes were analysed in terms of the relationship of D90 to prostate-specific antigen relapse-free survival (nadir 2+ definition) and all patients had a minimum follow-up of 5 years. For contemporary patients from 2011, quality metrics from post-implant computed tomography as defined by RCR guidelines are presented. Results: A mean D90 of 138.7 Gy (standard deviation 24.7) was achieved for the historic cohort. Biochemical control at 10 years was 76% in patients with D90 > 140 Gy and 68% in those with D90 < 140 Gy ( P  < 0.01). In current practice, over the last 3 years the mean (standard deviation) D90 has increased from 154 (15.3) Gy in 2011 to 164 (13.5) Gy in 2013. Similarly, an increase in the mean (standard deviation) V100 from 92 (4.4) to 95 (3.2) % is noted over time. No difference between clinicians was noted. Conclusion: D90 values of less than 140 Gy continue to be predictive of increased risk of recurrence of prostate cancer across risk groups with longer follow-up. Quality assurance can be used to ensure improved and consistent implant quality in a team with multiple clinicians. Highlights: We document prostate-specific antigen (PSA) control rates in 2157 men treated with iodine-125 prostate brachytherapy. PSA control is compared with computed tomography post-implant dosimetry. Long-term PSA control is 8% higher with D90 > 140 Gy. Current practice is audited against RCR guidelines. Routine post-implant dosimetry is associated with better quality.